Remarkable lives: Andrew Aldred in conversation with Jerome Carson. Issue 3 (5th August 2014) - Carson, Jerome; Aldred, Andrew
Abstract : Purpose: – The purpose of this paper is to offer a profile of Andrew Aldred. Design/methodology/approach: – Andrew provides a short biography and is then interviewed by Jerome. Areas covered in the interview include Andrew's experiences during the Falklands War, his poetry and his time in hospital care. Findings: – His experiences in the Falklands War brought home to Andrew the trauma of war as well as its futility. Its personal effects proved long lasting. His descent into mental illness led to years of institutional care and terrible physical complications as a result of the medications he was given. Research limitations/implications: – One person's account of the factors influencing their recovery. Practical implications: – Offers insights into the recovery process and the factors that can facilitate this. Social implications: – Emphasises the importance of social factors in the recovery process. Originality/value: – Andrew's story shows his long journey of recovery from his Falklands War experiences to prolonged hospital incarceration. Poetry helped him process these experiences and finding his wife gave him the support and love to rebuild his life.